30th birthday celebrations: Views from the top about future management research and practice - Ratten, Vanessa; Newman, Alexander; Palacios-Marqués, Daniel; McKeown, Tui; Casais, Beatriz; Prentice, Catherine; Núñez-Sánchez, José Manuel; Liñán, Francisco; Stanton, Pauline; Le, Huong; Aseri, Mosa Amer; Walton, Sara (Cambridge University Press, 2026)
This perspective article is to celebrate the 30th birthday of the Journal of Management & Organization. To remember its achievements and to reflect on its successes a number of management academics were quizzed about their thoughts. This helps to identify future growth areas of management interest and to project new developments. By doing so it enables a holistic view about the role of management in practice, policy and society.
Celebración del 30 cumpleaños: Perspectivas desde la cúpula sobre la investigación y la práctica de la gestión futura.
Keywords: Empresas - Gestión; Management; Business research; Managers; Community; Scholarship